Retroperitoneal Sclerosing Lipogranuloma in an Adolescent With Congenital Atresia of the Inferior Vena Cava: Case Report and Literature Review. Issue 4 (May 2021) - Lamoshi, Abdulraouf; Rothstein, David H.; Ham, Phillip Benson; Khan, Abdur; Cheney, Richard; Williot, Pierre; Twist, Clare; Schaefer, Beverly
Abstract : Sclerosing lipogranuloma (SLG) in children is a rare, benign disease of unknown etiology suspected to be due to abnormal fatty tissue reaction. A 13-year-old girl presented with progressively worsening back pain. Cross-sectional imaging identified a retroperitoneal mass compressing the left ureter as well as infrarenal inferior vena cava atresia with extensive venous collaterals and chronic partially occlusive thromboses of the iliac veins. Surgical biopsy was consistent with SLG and it resolved spontaneously. SLG is typically a disease of adulthood but may be seen in children. The association between inferior vena cava atresia with venous thrombosis and development of SLG has not been reported previously.